Soldier‐biased gene expression in a subterranean termite implies functional specialization of the defensive caste. Issue 1 (23rd November 2017) - Wu, Tian; Dhami, Gurpreet K.; Thompson, Graham J
Abstract : In a termite colony, reproduction is typically monopolized by a small number of sexuals that are supported by reproductively altruistic soldiers and workers. We expect caste differentiation to be associated with clear‐cut differences in gene expression, and for these differences to reflect caste function and development. Here, we use RNA‐Sequencing to compare the gene expression profiles of sexual nymphs and two non‐reproductive helper castes (i.e., workers and soldiers) of the Eastern subterranean termite Reticulitermes flavipes . We found that of n  = 93 genes that are strictly expressed as a function of caste, a majority (78%) show a soldier‐specific pattern. This conspicuous soldier‐bias in genome‐wide expression suggests that this defensively specialized caste is functionally well‐differentiated from both the reproductive and the other non‐reproductive caste of this species, despite a shared developmental program with workers. Gene ontology analysis supports the notion of functional specialization by soldiers, as soldier‐biased gene sets are enriched for novel biological processes. Whether this pattern reflects ancient or more recent bouts of selection for caste novelty at the gene‐regulatory level is not known, but because soldiers are sterile and thus have no direct fitness, any selection for novelty must have been mediated indirectly, through reproducing relatives.